Serological and Non-Sputum Biomarkers for Tuberculosis Diagnosis: A Systematic Review of Host- and Pathogen-Derived Signatures - Wa Ode Diah Erwati; Andriansjah Rukmana (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2025)
Tuberculosis (TB) remains a major global health concern, with more than 10 million new cases reported annually. Conventional sputum-based diagnostics such as microscopy, culture, and GeneXpert MTB/RIF show limited sensitivity in children, individuals with HIV, and extrapulmonary TB, highlighting the need for accurate non-sputum alternatives. This systematic review evaluates the diagnostic performance of serological and other non-sputum biomarkers for active TB, focusing on both host and pathogen derived targets. Eleven eligible studies (2016–2024) involving 2,548 participants were analyzed. The reviewed studies employed multiplex immunoassays and protein microarrays to assess immune markers and M. tuberculosis antigens. Key findings indicate that several cytokines (e.g., IFN-γ, IP-10, IL-27) and antibodies to ESAT-6, CFP-10, and Ag85B differentiated active from latent infection. Multi-antigen panels achieved sensitivity and specificity above 85%, while saliva, serum, and skin-based assays showed potential for non-invasive and field-applicable diagnosis. The novelty of this review lies in its integrative approach analyzing both host and pathogen biomarkers, which are often studied separately. Such multi-marker, non-sputum serological strategies could complement current TB diagnostics and provide reliable, accessible tools for use in resource-limited and high HIV prevalence settings